Starving PTEN-deficient prostate cancer cells thrive under nutrient stress by scavenging corpses for their supper. (4th July 2018) - Jayashankar, Vaishali; Finicle, Brendan T.; Edinger, Aimee L.
ABSTRACT: Our recent work demonstrates that inactivating mutations in phosphatase and tensin homolog ( PTEN ) are sufficient to drive macropinocytosis in the context of AMP-activated protein kinase (AMPK) activation. Given that blocking macropinocytosis limits PTEN-deficient prostate tumor growth, AMPK or phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K) inhibitors could have therapeutic value in castration-resistant prostate cancer patients, particularly when used in combination with standard of care therapies. Abbreviations: ATG5: autophagy related 5; NHE: Na(+)/H(+) exchanger; PAK1: p21-activated kinase 1; PI3K: phosphatidylinositol-4, 5-bisphosphate 3-kinase; PIP3 : phosphatidylinositol (3, 4, 5)-trisphosphate; PIP2 : phosphatidylinositol (4, 5)-bisphosphate; RAC1: Rac family small GTPase 1